Legal Cannabis sativa L. Dried Inflorescences: Cannabinoids Content and Cytotoxic Activity against Human HepG2 Cell Line - Maria Assunta Acquavia; Carmen Tesoro; Raffaella Pascale; Angela Ostuni; Ilenia Matera; Giuliana Bianco; Laura Scrano; Sabino A. Bufo; Rosanna Ciriello; Angela Di Capua; Filomena Lelario (Applied Sciences, 2023)
Cannabis sativa L. has health benefits, principally due to the levels and ratios of two important cannabinoids, Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD). THC:CBD ratio affects their pharmacological interaction for the treatment of different diseases as well as its modulation allows for a custom-made product that utilizes the distinguishing effects of CBD, THC, or both, for a peculiar patient or clinical effect. This study aims to investigate the total content of THC, CBD, and their ratio in 34 dried inflorescence legally sold in physical and online stores, by using a validated liquid chromatography-ultraviolet (HPLC-UV) method, after cannabinoids identification performed through MSn studies. Cannabinol (CBN) content was also monitored to evaluate hemp age or conservation status. CBN content always resulted lower than limit of quantification, thus confirming well-stored fresh hemp. All investigated samples showed a total THC amount below 0.59% w/w, thus responding to legal requirements.. The total CBD amount ranged from 2.62 to 20.27% w/w and it was not related to THC level. THC:CBD ranged among 1:3 and 1:26, thus ascertaining their suitability for different target pharmacological uses. In vitro studies using human hepatoblastoma cell line HepG2 suggested that hemp extracts with THC:CBD ratios of 1:9 exhibited higher toxicity than pure cannabinoids.